A local network for extracorporeal membrane oxygenation in refractory cardiogenic shock. (2nd October 2015) - Dini, Carlotta Sorini; Lazzeri, Chiara; Chiostri, Marco; Gensini, Gian Franco; Valente, Serafina
Abstract : Background: Veno-arterial extracorporeal membrane oxygenation (VA ECMO) represents a therapeutic option in patients with refractory cardiogenic shock (RCS). This strategy is limited to a restricted number of centres with capabilities for implanting VA ECMO and management patients on this support. We report on the initial experience of our ECMO referral centre for patients with RCS. Methods: We retrospectively analysed our ECMO data registry for RCS of 14 patients treated with VA ECMO, consecutively admitted to our intensive cardiac care unit (ICCU), which is an ECMO referral centre. Results: Six patients (6/14, 42%) came from peripheral centres, four were transferred to our ICCU directly. During ICCU stay, four patients died (28.5%) due to multi-organ failure, seven showed a complete recovery while one underwent cardiac transplantation. The remaining two patients died while waiting for cardiac transplantation because of cerebral haemorrhage. The 30-day overall mortality rate was 42.8%, all survivors showed a good neurologic outcome. Conclusions: In our series, the survival rate of RCS patients supported by VA ECMO is high (57%) and the transfer of RCS patients is feasible and safe. Our data support that a network for RCS is needed to transfer patients in well experienced centres even on ECMO support.